Anthi Beka, The Active Role of Courts in Consumer Litigation. Applying EU Law of the National Courts’ Own Motion, Intersentia, Cambridge-Antwerp-Chicago, 2018, 375 págs - Esteban de la Rosa, Fernando (Revista de Derecho Comunitario Europeo, 2020)
Sin resumen